2020
DOI: 10.1038/s42005-020-0309-3
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of excitonic emission crossing Saha equilibrium in trap passivated CH3NH3PbBr3 perovskite

Abstract: Metal-halide semiconductor perovskites have received great attention for the development of stable and efficient light emitting diodes and lasers, since they combine high charge carrier mobility and light emission spectral-purity with low-cost fabrication methods. Nevertheless, the role of excitons, free carries and trap states in perovskite light emission properties is still unclear due to their interdependence. In this paper we selectively manage trapping and light emission mechanisms by a reversible laser-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 59 publications
4
29
0
Order By: Relevance
“…According to data published by other authors [64], B ranges between 2×10 −11 and 1.4×10 −10 cm 3 s −1 , so we believe that our assumptions above provides realistic results. Finally, D can be calculated as 1/N 0 τ f , where τ f is a formation time for excitons (approximately 1 fs), and hence D = 10 −4 cm −3 s −1 , in agreement with experimental data reported by other authors [28]. In these conditions, DK B.…”
Section: Appendix A: Calculation Of Excitation Fluencesupporting
confidence: 88%
See 3 more Smart Citations
“…According to data published by other authors [64], B ranges between 2×10 −11 and 1.4×10 −10 cm 3 s −1 , so we believe that our assumptions above provides realistic results. Finally, D can be calculated as 1/N 0 τ f , where τ f is a formation time for excitons (approximately 1 fs), and hence D = 10 −4 cm −3 s −1 , in agreement with experimental data reported by other authors [28]. In these conditions, DK B.…”
Section: Appendix A: Calculation Of Excitation Fluencesupporting
confidence: 88%
“…4(c)] due to the finite density of states in the first case. Similar analysis carried out on passivated CH 3 NH 3 PbBr 3 perovskite thin films also concluded that excitons play a major role in the PL spectrum, which is even underestimated by the population predicted by Saha's equation [28].…”
Section: B Analysis Of Spontaneous Emission and Ase Spectramentioning
confidence: 56%
See 2 more Smart Citations
“…The spectrum of the pristine sample (black curve) shows the typical Wannier-Mott excitonic peak (here referred to as T1) generally observed in the absorption spectrum of this material. 34 , 35 T1 disappears as soon as the first X-ray dose is delivered, revealing the band-to-band absorption edge and a new peak at lower energies (T2), which increases proportionally to the absorbed dose. This effect cannot be ascribed to sample aging, as demonstrated by the consistency in time of the SPS spectra of a control sample ( Figure 1 b), which was not exposed to X-ray radiation.…”
Section: Resultsmentioning
confidence: 99%